Hardness, polymerization depth, and internal adaptation of Class II silorane composite restorations as a function of polymerization protocol - Bechtold, Janaina; dos Santos, Priscila Jaques; Anido-Anido, Andrea; Hipólito, Vinícius Di; Alonso, Roberta Caroline Bruschi; D’Alpino, Paulo Henrique Perlatti (European Journal of Dentistry, 2012)
Objectives: To evaluate the influence of various photoactivation techniques on the internal gap, Knoop-hardness, and polymerization depth of silorane-and methacrylate-based composites in Class II restorationsMethods: Preparations were made in third molars (n = 10), according to composites (Filtek P60: methacrylate; Filtek P90: silorane) and photoactivation techniques (OC: occlusal photoactivation (control); OBL: occlusal+buccal+lingual photoactivation; and BLO: buccal+lingual+occlusal photoactivation (transdental)). Composites were inserted in two increments, both individually photoactivated for 20s. After 24h, specimens were sectioned and the ratio of internal gaps to interface length (%) recorded. Hardness was tested across the transversal section of restorations (1-4 mm below the surface)Results: Silorane restorations showed significantly lower gaps compared with methacrylate, regardless of polymerization technique (P<.05). Supplementary energy dose in OBL and BLO protocols caused significant increase in gaps in silorane restorations (P<05). For methacrylate restorations, OBL activation caused significantly higher gap formation (P<.05). Significantly lower hardness values were seen for silorane than for methacrylate composites (P<.05), regardless of depth and photoactivation. Significantly higher hardness values were seen in BLO activation for methacrylate restorations compared with control (P<05); for silorane, no differences were observed. Significantly higher hardness values were observed at 1 and 3 mm compared to 2 and 4 mm for both compositesConclusions: Internal gaps and hardness are affected by composite type and photoactivation. Despite the reduced values, hardness of silorane is not influenced by photoactivation or by depth. Internal gaps are dependent on the energy dose for both composites, with silorane showing lower internal gaps. (Eur J Dent 2012;6:133-140)
Keywords: Dental composites; Knoop hardness; polymerization; internal adaptation